Evaluating composting and co-composting kinetics of various agro-industrial wastes - Hani Abu Qdais; Mohamad Al-Widyan (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Agro-industrial wastes are posing serious challenges for the agro-industries. Composting and co-composting of such wastes will lead to converting such wastes into a useful product that will serve as a soil conditioner. The present research investigated the kinetics of composting and co-composting of several agro-industrial wastes. Methods Seven pilot scale composting and co-composting piles of substrates from grain dust (GD), coffee-processing waste (CPW) and olive mill waste (OMW) were tested. Temperature and moisture content of the piles were monitored during the composting process and adjusted whenever necessary. Results The biodegradation kinetics was found to be of first order for all composting and co-composting piles. As judged by the value of the reaction rate constant, and the temperature of the piles, the biodegradability of the grain dust was the highest among all composting piles, followed by the coffee-processing residue and finally the fresh olive mill waste. As for the co-composting, the highest degradability was noticed in the pile that was composed of grain dust and coffee-processing waste followed by that of grain dust mixed with dry olive mill waste, and then followed by coffee-processing waste and dry olive mill waste and finally by grain dust with fresh olive-processing waste. Conclusions Composting and co-composting of agro-industrial wastes is a low cost and an environmentally friendly waste management option for solving the problem of the disposal of such waste. The study revealed that all piles followed first-order kinetics with different biodegradability rates.